Recours a la Médecine Traditionnelle chez les Rhumatisants en Guinée - Kamissoko Aly Badra; Traoré Marie; Wann Thierno Amadou; Baldé Mamadou Dian; Diallo Mamadou Lamine; Oniankitan Sadat; Camara Alpha Ketty; Awada Mohamed; Diallo Alhassane; Oniankitan Owonayo (European Scientific Journal, ESJ, 2019)
Aim: To determine the frequency and pattern of use of traditional medicine in rheumatic patients at Ignace Deen National Hospital in Conakry, Guinea. Patients and methods: Descriptive cross-sectional study in the rheumatology department of HNID between January and March 2018 Results: Of the 108 patients interviewed, 40 had used traditional medicine (37.03%). There was a female predominance (21 women, 52.5%) with a sex ratio of 0.90. The mean age of the patients was 44.75 ± 17.24 years. Rheumatoid arthritis and knee osteoarthritis were the main rheumatic diseases observed with 41.86% and 16.27% respectively. The diagnostic delay was 6.54 ± 1.25 years. The nature of the treatment used was dominated by taking a decoction (57.50%) and the reason for using traditional treatment was to relieve pain (85%). The oral route was the main mode of use of traditional treatment (67.5%). More than half of the patients (52.50%) were not satisfied with the outcome of traditional treatment received and did not know the name of the treatment used in their vernacular language. In 47.50% of cases they thought that traditional treatment had adverse effects and had possible interactions with modern drug therapy. Conclusion: More than a third of rheumatology consulting patients use traditional medicine even though they believe it has side effects. This phenomenon leads to a delay in consultation with the rheumatologist, hence the need for better communication between the different actors.Objectif : Déterminer la fréquence et le profil de l’utilisation de la médecine traditionnelle chez les patients souffrant de rhumatisme à l'hôpital national Ignace Deen de Conakry (Guinée). Patients et méthodes : Etude transversale de type descriptif dans le service de rhumatologie de l'HNID entre janvier et mars 2018. Résultats : Sur 108 patients interrogés, 40 avaient eu recours à la médecine traditionnelle soit 37,03 %. On notait une prédominance féminine (21 femmes ; 52,5 %) avec un sexe ratio de 0,90 H/F. L’âge moyen des patients était de 44,75 ± 17,24 ans. La polyarthrite rhumatoïde et la gonarthrose étaient les principales affections rhumatologiques observées avec respectivement 41,86% et 16,27%. Le délai diagnostique était de 6,54 ±1,25 ans. La nature du traitement utilisé était dominée par la prise de décoction (57,50%) et le motif d’utilisation du traitement était de soulager la douleur (85%). La voie orale était le principal mode d’utilisation (67,5%). Plus de la moitié des patients (52,50%) n’étaient pas satisfaits du résultat du traitement traditionnel reçu et ne connaissaient pas le nom du traitement utilisé dans leur langue vernaculaire. Ils pensaient dans 47,50% des cas que le traitement traditionnel entrainait des effets indésirables et avait de possibles interactions avec le traitement médicamenteux moderne. Conclusion : Plus du tiers des patients consultant en rhumatologie ont recours à la médecine traditionnelle même s’ils croient qu’elle a des effets indésirables. Ce phénomène entraîne un retard à la consultation chez le rhumatologue, d’où la nécessité d’une meilleure communication entre les différents acteurs.